Primary School Teachers’ Understanding of Essential Science Concepts - Ari Widodo; Diana Rochintaniawati; Riandi Riandi (Jurnal Cakrawala Pendidikan, 2017)
Abstract: Teacher’s understanding of science is a prerequisite for teaching science. Due to the lack of science background during their studies, some primary school teachers have limited understanding of science. This study aims at identifying primary school teacher’s understanding of essential science concepts. Data were collected from 293 participants of workshops of professional certification program at university. Teacher’s understanding was measured using a multiple choice test whose answers are in the form of degree of certainty. The study finds that many teachers do not have good understanding of science. Misconceptions are also identified in a number of areas. Student textbooks, myths spread over in the communities, and narrow interpretation of religious teaching are some sources of teacher’s misconceptions. These findings suggest that future professional development program for primary school teachers should be designed in the areas of subject matters and subject matter pedagogy. Keywords: elementary school teachers, misconception, science, understanding